Impact of new accounting policy framework in property, plant and equipment and inventories of popular housing case (2016)
This essay seeks to establish the main impacts will be generated in the convergence of the previous regime to the New Accounting Regulatory Framework in relation to property, plant and equipment and inventories of the Popular Housing Fund. It assesses whether movables and properties meet the characteristics of assets described in the New Framework for the preparation and presentation of financial information from government entities. Are recognized as assets, resources controlled by the entity resulting from a past event and which is expected to obtain service potential or generate future economic benefits, provided that the resource value can be measured reliably. It is also important to consider for the evaluation of control for the New Legal Framework Accounting premium the economic over the legal.